The Effectiveness of the Rehabilitation of Islamic Boarding Schools Responsibilities as a Method of Healing of Drug Abuser - Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This research aims to know about rehabilitation, narcotics addicts and narcotics abusers who are proven victims are required to undergo and carry out medical rehabilitation or undergo social rehabilitation. In terms of social rehabilitation, Article 57 of Act No. 35 of 2009 states that